Board Expertise, Female Gender Representation and Corporate Financial Misconduct in Nigeria: A Mediating Effect Analysis - Sunday Otuya (Copernican Journal of Finance & Accounting)
The objective of this study is to investigate the mediating effect of female gender representation on the nexus between board expertise and incidence of corporate financial misconduct. The study was anchored on the agency theory and adopted a panel research design. Population of the study was made up of all manufacturing firms listed on the Nigeria Exchange Group (NGX) as at 31st December 2023. Findings of the study show that board expertise significantly reduces the likelihood of financial misconduct while female board representation has no significant positive effect. The joint effect of board expertise and female board representation was positive indicating the inclusion of women on board weakens the positive effect of board expertise on financial misconduct. Ensuing from our findings, we recommend that companies should place emphasis on professional experience and educational qualification rather than gender diversity in appointments to boards.